Trst, Ljubljana, Zagreb in Beograd med obrobjem in središčem - Toporišič, Tomaž (Amfiteater (Ljubljana), 2023)
The essay outlines two attempts to revolutionise the relationship between the periphery and the centre in Central and Eastern Europe. The first belongs to the historical avantgardes of the 1920s and 1930s. The second one belongs to the retro-avant-gardes at the turn of the century, which re-enacted some of the basic ideas of Constructivist and Futurist utopian questions. The retro-generations announced that they were the heirs of the artistic generation of the Constructivists and Zenitists, who wanted to promote Ljubljana, Zagreb, Belgrade and Trieste as centres of new art to establish a new bridge between East and West.
Keywords: Černigoj, Avgust; Delak, Ferdo; historical avant-gardes; horizontal history of art; horizontalna zgodovina umetnosti; Micić, Ljubomir; retroavantgarde; retro-avant-gardes; zgodovinske avantgarde